Morphometric Analysis of the Human Femur, Correlations with Age, Sex, and Stature in a Pakistani Population - Zaffar Iqbal Malik, Ahmad Yar, Muhammad Faisal Khan, Rabia Rauf, Sibtain Raza, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The human femur is the longest and strongest bone of the skeleton, providing critical information in forensic anthropology and clinical practice. Its morphometric characteristics are highly reliable for estimating sex, stature, and age. Although femoral morphometry has been extensively studied in various global populations, there is a lack of population-specific data for Pakistan, where genetic, nutritional, and environmental factors may influence skeletal dimensions. Objectives: This study aimed to analyze morphometric parameters of the human femur and assess their correlation with age, sex, and stature in a Pakistani population. Methods: A descriptive cross-sectional study was conducted between January 2023 and June 2023 at the Anatomy Department, Sahara Medical College, Narowal, and the Anatomy Department of University of Lahore Teaching Hospital, Lahore. A total of ninety human femora with documented demographic details were examined. Maximum femoral length, head diameter, bicondylar width, and midshaft circumference were measured using osteometric board and digital calipers. Demographic data were obtained from cadaveric records. Statistical analysis was performed using SPSS v26, applying descriptive statistics, independent t-tests, Pearson’s correlation, and linear regression. Results: Male femora demonstrated significantly larger measurements compared to female femora (p < 0.01). Maximum femoral length exhibited the strongest correlation with stature (r = 0.81, p < 0.001), followed by femoral head diameter (r = 0.64, p < 0.01). Regression analysis produced the pooled equation: Stature (cm) = 68.21 + 2.18 × Maximum Femoral Length (cm) with R² = 0.62. Femoral head diameter showed a weak negative correlation with age (r = -0.23, p = 0.04). Conclusion: Femoral morphometry displays clear sexual dimorphism and strong correlation with stature in the Pakistani population. Maximum femoral length is the most reliable predictor of height, while femoral head diameter contributes supportive value. These findings establish baseline reference data for forensic and clinical applications in Pakistan. Keywords: Femur, Morphometry, Stature estimation, Sexual dimorphism, Forensic anthropology, Pakistani population